2019
DOI: 10.1155/2019/1359528
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Degradation and Production of Extracellular Cholesterol Oxidase fromBacillus pumilusW1 andSerratia marcescensW8

Abstract: Cholesterol is a waxy substance present in all types of the body cells. The presence of higher concentration of low density lipoprotein (LDL) is characterized by abnormal cholesterol level and is associated with cardiovascular diseases which lead to the development of atheroma in arteries known as atherosclerosis. The transformation of cholesterol by bacterial cholesterol oxidase can provide a key solution for the treatment of diseases related to cholesterol and its oxidized derivatives. Previously isolated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…The intracellular or extracellular cholesterol oxidase produced by a variety of microorganisms, including Streptomyces natalensis [6] Streptomyces cavourensis [14], Mycobacterium tuberculosis [9], Chromobacterium sp. DS1 [15], Bacillus pumilus W1 and Serratia marcescens W8 [16]. In case of pathogenic bacteria, cholesterol oxidases serve as membrane destroying agents and thus contribute to their pathogenicity as a virulence factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular or extracellular cholesterol oxidase produced by a variety of microorganisms, including Streptomyces natalensis [6] Streptomyces cavourensis [14], Mycobacterium tuberculosis [9], Chromobacterium sp. DS1 [15], Bacillus pumilus W1 and Serratia marcescens W8 [16]. In case of pathogenic bacteria, cholesterol oxidases serve as membrane destroying agents and thus contribute to their pathogenicity as a virulence factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cholestenone, which is produced as a metabolite, is safe and can be used to control obesity, treat liver disease, and prevent keratinization of the skin ( Elia et al, 2019 ). Wali et al (2019) isolated Bacillus pumilus W1 and Serratia marcescens W8 from soil contaminated with oil and reported that these strains degrade cholesterol and produce red colonies in M9 medium containing 0.1% cholesterol as the only carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…The literature suggests that cholestenone can be produced by a limited number of microbes that infect humans including Mycobacteria , Rhodococcus, and Nocardia ( 54 ). In addition, we performed a literature review on the top bacterial causes of pulmonary infections and only identified reports of cholesterol oxidase activity by ChoD orthologs in Acinetobacter ( 55 ), Pseudomonas ( 56 58 ), and Serratia ( 59 ). However, there are several studies showing that putative cholesterol oxidases of Pseudomonas produce hydroperoxycholestenone (HCEO) rather than cholestenone ( 56 58 ).…”
Section: Discussionmentioning
confidence: 99%